2017
DOI: 10.18869/acadpub.jafm.73.240.26847
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Generation and Optimization of Laminar Forced Convection Air Cooling in a Horizontal Channel Containing Heated Sources

Abstract: A forced convection air-cooling of two identical heat sources mounted in a horizontal channel is numerically studied. Four effects of Reynolds number, separation distance, height and width of the components on the flow structure and heat transfer inside the channel have been examined. The entropy generation minimization method (EGM) is employed to optimize the heat transfer and fluid flow in the channel. The flow field is governed by the Navier-Stokes equation and the thermal field by the energy equation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The model is empirically developed via regression from various response values or simulations. The numerical simulation outcomes were evaluated using the outcome of the surface interpolation process utilizing the subsequent second-order polynomial equation [29][30][31]:…”
Section: Response Surface Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The model is empirically developed via regression from various response values or simulations. The numerical simulation outcomes were evaluated using the outcome of the surface interpolation process utilizing the subsequent second-order polynomial equation [29][30][31]:…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…where x i is the i th individual parameter of the empty encoded value, the uncoded value of the i th independent parameter is indicated by X i * similarly, at the middle point, the uncoded value of the i th individual parameter is designated by x ij , and the variation in the step value has been described as ∆X i [31].…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…The entropy generation induced by forced convection air cooling process from heated sources in a channel was numerically analyzed by Bensouici and Bensouici. 4 They observed that the increase of separation distance, height, and width of the components cause an increase in the total entropy generation and the average Nusselt number. Davalath and Bayazitoglu 5 studied the forced convection from several heat-conducting rectangular bodies in a channel.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the MHD effects lessened the convective heat transport leading to further increment in conductive heat transport, the aspect ratio of the enclosure has considerably affected the temperature, concentration and velocity profiles. Bensouici and Bensouici (2017) have numerically applied the entropy generation minimization theory to optimize the heat transfer and the liquid motion in a horizontal channel to lessen the energy loss and to promote the cooling of heat sources. They obtained that a better configuration for highest heat transfer and minimum entropy was reached for the optimal Re number, separation distance, width and height of heat source, which are equal to 50, 1, 0.25 and 0.25, respectively.…”
Section: Introductionmentioning
confidence: 99%